MXene / modified polymer aerogel and preparation method and application thereof

CN117156831BActive Publication Date: 2026-10-20JIANGHAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210621100.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-05-24
Filing Date
2022-06-01
Publication Date
2026-10-20
Estimated Expiration
2042-06-01

AI Technical Summary

Technical Problem

同时,MXene在材料中的含量会影响工艺条件,要控制MXene比例具有一定难度

Benefits of technology

1.选择单层MXene作为导电填料。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117156831B_ABST
    Figure CN117156831B_ABST
Patent Text Reader

Abstract

The application discloses MXene / modified polymer aerogel as well as a preparation method and application thereof, and the preparation method comprises the following steps: firstly, 3ml of 10mg / ml MXene dispersion liquid is taken; then, 15-60mg of dopamine grafted sodium hyaluronate is added; after the dopamine grafted sodium hyaluronate is completely dissolved, 12-48mg of sodium tetraborate is added; the stirring is continuously carried out for 30min; then, the mixture is placed into a container containing liquid nitrogen, so that the metal base of a mold is in contact with the liquid nitrogen to perform directional freezing; the mixture is placed in a freezing dryer under-10 DEG C for 2h to perform freezing drying, and thus the MXene / modified polymer aerogel is obtained. The dopamine modified sodium hyaluronate and the sodium tetraborate are used as a skeleton supporting material, and the single-layer MXene is used as a conductive filler, so that the prepared MXene aerogel has the advantages of light weight, high conductivity, excellent electromagnetic shielding performance and good mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aerogel preparation, specifically to an MXene / modified polymer aerogel and its preparation method, and also to the application of the MXene / modified polymer aerogel prepared by this method. Background Technology

[0002] In recent years, with the rapid development of fifth-generation (5G) communication technology and portable devices, electromagnetic radiation pollution has become a global problem, attracting widespread attention from researchers worldwide. Developing efficient electromagnetic interference shielding materials is necessary and urgent for protecting precision equipment and human health from external radiation. Currently, domestic electromagnetic shielding materials suffer from problems such as high density, susceptibility to damage, and difficulty in processing.

[0003] Transition metal carbides / nitrides (MXenes) are emerging two-dimensional materials that have attracted widespread attention and research since their discovery in 2011. MXenes are widely used in electromagnetic shielding due to their high metallic conductivity and high reflectivity to electromagnetic waves. However, MXenes typically exist macroscopically in powder or thin film form, with an extremely dense structure leading to high density. Furthermore, MXenes have weak self-assembly capabilities, preventing them from independently forming stable three-dimensional structures, which severely hinders their application in electromagnetic shielding. Aerogels, with their large specific surface area, tunable pore size, tunable framework, and unique surface properties, are ideal electromagnetic shielding materials. Assembling MXenes as a dispersed phase with polymers is currently an effective method for preparing MXene aerogels.

[0004] Currently reported materials that utilize polymers to mix with MXene suspensions include gelatin, polyacrylic acid, and sodium alginate. However, MXene exhibits poor dispersibility in high-viscosity systems, failing to form an effective conductive network and thus affecting electromagnetic shielding performance. Furthermore, MXene is easily oxidized, so stirring time should not be excessive when mixing with other materials; time control is necessary to ensure complete mixing. Additionally, the MXene content in the materials affects process conditions, making it challenging to control the MXene ratio. Summary of the Invention

[0005] To address the aforementioned problems in the existing technology, the present invention aims to provide an MXene / modified polymer aerogel and its preparation method. This method utilizes dopamine-modified sodium hyaluronate and sodium tetraborate as the skeletal support materials, and a single layer of MXene as the conductive filler. The resulting MXene aerogel exhibits lightweight, high conductivity, excellent electromagnetic shielding performance, and good mechanical properties.

[0006] Another objective of this invention is to provide an application of the MXene / modified polymer aerogel prepared by the above method in electromagnetic interference shielding, which has a good electromagnetic shielding effect.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: a method for preparing MXene / modified polymer aerogel, comprising: First, take 3 ml of 10 mg / ml MXene dispersion, then add 15-60 mg of dopamine-grafted sodium hyaluronate (HAC). After it is completely dissolved, add 12-48 mg of sodium tetraborate and continue stirring for 30 minutes. Then, place it in a container filled with liquid nitrogen, so that the metal base of the mold is in contact with the liquid nitrogen for directional freezing, and freeze it at -10°C for 2 hours. Then, place it in a freeze dryer for freeze drying to obtain MXene / modified polymer aerogel.

[0008] Optionally, the preparation steps of the dopamine-grafted sodium hyaluronate include: Step 1: Prepare 0.01 mol / L PBS buffer solution (1 L): Weigh 7.9g sodium chloride, 0.2g potassium chloride, 0.24g potassium dihydrogen phosphate and 1.8g dipotassium hydrogen phosphate and add them to a 500ml beaker containing 300mL deionized water. Dissolve the solution by magnetic stirring at room temperature, then transfer it to a 1L volumetric flask and add deionized water to make up to the final volume to obtain a 0.01mol / L PBS buffer solution. Store the solution at 4℃ after preparation. Step 2: Preparation of dopamine-grafted sodium hyaluronate: 1) Weigh 1g of sodium hyaluronate at room temperature and place it in a three-necked flask. Add 100mL of 0.01mol / L PBS buffer solution and stir until the sodium hyaluronate is completely dissolved. Then adjust the pH of the solution to about 5. Then add 0.286g of N-hydroxysuccinimide (NHS) and 0.476g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) catalyst in sequence. After they are fully dissolved by stirring, purge with nitrogen for 30min to prevent dopamine from being oxidized. Add 0.566g of dopamine and react in an ice bath for 12h. 2) Place the crude product after the reaction in a dialysis bag with a molecular weight cutoff of 14 kDa, and dialyze it with deionized water for 2 days, changing the deionized water every 12 hours to remove the residual catalyst and unreacted monomers in the solution to obtain the grafted product. Freeze-dry the dialyzed solution to obtain dopamine-grafted sodium hyaluronate.

[0009] The reaction is as follows: .

[0010] Therefore, this invention uses MXene and polymer doping to create an aerogel, thereby reducing the density of the composite material. By doping MXene with HAC (dopamine grafted onto sodium hyaluronate), the phenolic hydroxyl groups on the HAC are preferentially oxidized, thus protecting MXene and slowing its oxidation in air, providing antioxidant capacity for the MXene-based composite aerogel. This solves the problems of difficult MXene stacking and molding, easy oxidation of MXene, and high overall material density.

[0011] Accordingly, this invention also claims protection for an MXene / modified polymer aerogel prepared by the aforementioned preparation method. The MXene / modified polymer aerogel has low density, good mechanical properties, antioxidant capacity, good electrical conductivity, and excellent electromagnetic shielding performance.

[0012] Accordingly, the present invention also claims the application of MXene / modified polymer aerogel prepared by the aforementioned preparation method in electromagnetic interference shielding, which has good electromagnetic shielding effect.

[0013] Compared with the prior art, the present invention has at least the following advantages: 1. Single-layer MXene was selected as the conductive filler.

[0014] MXene is an emerging two-dimensional material whose unique structure makes it particularly attractive for electrochemical energy storage and conversion applications. Monolayer MXene possesses functional groups such as -OH, -O, and -F on its surface, which can serve as binding sites for various organic or inorganic species, providing opportunities to construct complex and diverse three-dimensional MXene architectures. Furthermore, the presence of multiple functional groups on its surface endows MXene with excellent hydrophilicity, resulting in good processability.

[0015] 2. Choose dopamine-grafted sodium hyaluronate.

[0016] Mussels in the ocean secrete byssal proteins with super-strong adhesive properties, rich in dihydroxyphenylalanine, which firmly anchor the mussels to solid surfaces such as reefs, ship hulls, and ropes. Sodium hyaluronate, an inherent component of the human body, is a dextran uronic acid with a linear single-chain structure and numerous hydroxyl groups in its molecule. Due to its unique physicochemical properties, it is widely used in biomedicine, cosmetics, and other fields. This invention grafts dopamine onto the main chain of sodium hyaluronate through an amidation reaction, modifying it before using it as an aerogel framework. The resulting aerogel has low density and good mechanical properties.

[0017] 3. Utilize covalent borate ester bonds to slow down MXene oxidation.

[0018] The covalent borate ester bond formed by the condensation reaction between sodium tetraborate and cis-dihydroxyl groups serves as a protective agent, mitigating the easy oxidation of MXene in air and thus achieving an antioxidant effect, thereby maintaining the overall performance of the MXene aerogel. The borate ester bond is shown below: . Attached Figure Description

[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0020] Figure 1 The image shows the UV-Vis spectrum of HAC. Figure 2 H of dopamine-modified sodium hyaluronate (HAC) 1 NMR spectrum; Figure 3 Scanning electron microscope image of the MXene / modified polymer aerogel prepared in Example 1; Figure 4 The electromagnetic interference shielding performance of the MXene / modified polymer aerogel prepared in Example 1 is shown in the figure. Detailed Implementation

[0021] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the invention.

[0022] A method for preparing MXene / modified polymer aerogel includes the following steps: Step 1: Prepare 0.01 mol / L PBS buffer solution (1 L) Weigh 7.9g sodium chloride, 0.2g potassium chloride, 0.24g potassium dihydrogen phosphate and 1.8g dipotassium hydrogen phosphate and add them to a 500ml beaker containing 300mL deionized water. Dissolve the solution by magnetic stirring at room temperature, then transfer it to a 1L volumetric flask and add deionized water to make up to the final volume to obtain a 0.01mol / L PBS buffer solution. Store the prepared solution in a 4℃ refrigerator.

[0023] Step 2: Preparation of dopamine-grafted sodium hyaluronate (HAC) 1. Weigh 1g of sodium hyaluronate at room temperature and place it in a three-necked flask. Add 100mL of 0.01mol / L PBS buffer solution and stir until the sodium hyaluronate is completely dissolved. Then adjust the pH of the solution to about 5. Add 0.286g of N-hydroxysuccinimide (NHS) and 0.476g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) catalyst in sequence. After they are fully dissolved by stirring, purge with nitrogen for 30min to prevent dopamine from being oxidized. Add 0.566g of dopamine (DA) and react in an ice bath (temperature about 0℃) for 12h.

[0024] 2. The crude product after the reaction was placed in a dialysis bag with a molecular weight cutoff of 14 kDa and dialyzed with deionized water for 2 days, changing the deionized water every 12 hours. The purpose was to remove residual catalyst and unreacted monomers from the solution to obtain the grafted product. The dialyzed solution was then freeze-dried (using a freeze dryer under vacuum at approximately -50°C) to obtain dopamine-grafted sodium hyaluronate (HAC). The yield of the prepared HAC was approximately 80%, and the grafting rate was approximately 33%.

[0025] The reaction is as follows:

[0026] Step 3: Preparation of MXene / modified polymer aerogel First, take 3 ml of 10 mg / ml MXene dispersion, then add 15-60 mg of HAC. After it is completely dissolved, add 12-48 mg of sodium tetraborate and continue stirring for 30 minutes. Then, place it in a container filled with liquid nitrogen, ensuring the metal base of the mold is in contact with the liquid nitrogen for directional freezing. Freeze at -10°C for 2 hours, and then freeze-dry in a freeze dryer (cold trap temperature approximately -50°C) to obtain MXene / modified polymer aerogel.

[0027] like Figure 1 The image shows the UV spectrum of the dopamine-modified sodium hyaluronate prepared in this invention. The strong UV absorption peak at 280 nm indicates the benzene ring structure in dopamine, proving that the grafting was successful. There are no additional peaks at wavelengths exceeding 300 nm, indicating that the conjugated catechol of HAC has not been oxidized.

[0028] like Figure 2 The image shown is the NMR spectrum of the prepared dopamine-modified sodium hyaluronate. The grafting rate of dopamine was calculated to be approximately 33% based on the NMR spectrum.

[0029] Example 1:

[0030] A method for preparing MXene / modified polymer aerogel includes the following steps: Step 1: Prepare 0.01 mol / L PBS buffer solution (1 L) Weigh 7.9g sodium chloride, 0.2g potassium chloride, 0.24g potassium dihydrogen phosphate and 1.8g dipotassium hydrogen phosphate and add them to a 500ml beaker containing 300mL deionized water. Dissolve the solution by magnetic stirring at room temperature, then transfer it to a 1L volumetric flask and add deionized water to make up to the final volume to obtain a 0.01mol / L PBS buffer solution. Store the prepared solution in a 4℃ refrigerator.

[0031] Step 2: Preparation of dopamine-grafted sodium hyaluronate (HAC) 1. Weigh 1g of sodium hyaluronate at room temperature and place it in a three-necked flask. Add 100mL of 0.01mol / L PBS buffer solution and stir until the sodium hyaluronate is completely dissolved. Then adjust the pH of the solution to about 5. Add 0.286g of N-hydroxysuccinimide (NHS) and 0.476g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide (EDC) catalyst in sequence. After they are fully dissolved by stirring, purge with nitrogen for 30min to prevent dopamine from being oxidized. Add 0.566g of dopamine (DA) and react in an ice bath (temperature about 0℃) for 12h.

[0032] 2. The crude product after the reaction was placed in a dialysis bag with a molecular weight cutoff of 14 kDa and dialyzed with deionized water for 2 days, changing the deionized water every 12 hours. The purpose was to remove residual catalyst and unreacted monomers from the solution to obtain the grafted product. The dialyzed solution was then freeze-dried (using a freeze dryer under vacuum at approximately -50°C) to obtain dopamine-grafted sodium hyaluronate (HAC). The yield of the prepared HAC was approximately 80%, and the grafting rate was approximately 33%.

[0033] Step 3: Preparation of MXene / modified polymer aerogel First, take 3 ml of 10 mg / ml MXene dispersion, then add 15 mg of HAC. After it is completely dissolved, add 12 mg of sodium tetraborate and continue stirring for 30 min. Then place it in a container filled with liquid nitrogen, so that the metal base of the mold is in contact with the liquid nitrogen for directional freezing, and freeze it at -10°C for 2 h. Then place it in a freeze dryer for freeze drying (cold trap temperature approximately -50°C) to obtain MXene / modified polymer aerogel.

[0034] like Figure 3 The image shown is a scanning electron microscope (SEM) image of the MXene / modified polymer aerogel prepared in Example 1. The image was taken at 5 kV, revealing the microstructure of the hybrid aerogel from different angles. The oriented pore structure forms a three-dimensional framework, solving the MXene stacking problem.

[0035] like Figure 4 The figure shows the electromagnetic interference shielding performance of the MXene / modified polymer aerogel prepared in Example 1. Tested in the X-band (8.2-12.4 GHz), the value reached a maximum of 42 dB, indicating good electromagnetic shielding effect.

[0036] Example 2:

[0037] Based on Example 1, this example modifies the amounts of HAC and sodium tetraborate in step three, specifically as follows: Step 3: Preparation of MXene / modified polymer aerogel First, take 3 ml of 10 mg / ml MXene dispersion, then add 30 mg of HAC. After it is completely dissolved, add 24 mg of sodium tetraborate and continue stirring for 30 min. Then place it in a container filled with liquid nitrogen, so that the metal base of the mold is in contact with the liquid nitrogen for directional freezing, and freeze it at -10°C for 2 h. Then place it in a freeze dryer for freeze drying (cold trap temperature approximately -50°C) to obtain MXene / modified polymer aerogel.

[0038] Example 3:

[0039] Based on Example 1, this example modifies the amounts of HAC and sodium tetraborate in step three, specifically as follows: Step 3: Preparation of MXene / modified polymer aerogel First, take 3 ml of 10 mg / ml MXene dispersion, then add 60 mg of HAC. After it is completely dissolved, add 48 mg of sodium tetraborate and continue stirring for 30 min. Then place it in a container filled with liquid nitrogen, so that the metal base of the mold is in contact with the liquid nitrogen for directional freezing, and freeze it at -10°C for 2 h. Then place it in a freeze dryer for freeze drying (cold trap temperature approximately -50°C) to obtain MXene / modified polymer aerogel.

[0040] The density, conductivity, and mechanical properties of the MXene / modified polymer aerogels prepared in Examples 1-3 were tested. The density was calculated by the mass-to-volume ratio (m / v); the conductivity was obtained by a four-probe instrument (tested at room temperature); and the mechanical properties were obtained by compression testing using a universal tensile testing machine (compression rate of 5 mm / min at room temperature). The results are shown in Table 1.

[0041] Table 1

[0042] Test results show that the overall performance of the MXene / modified polymer aerogel prepared in Example 1 is better than that of the MXene / modified polymer aerogel prepared in Examples 2 and 3. Specifically, the MXene / modified polymer aerogel prepared in Examples 2 and 3 has a higher density and lower conductivity than that prepared in Example 1. The mechanical properties of the MXene / modified polymer aerogel prepared in Examples 2 and 3 are slightly better than those prepared in Example 1. This indicates that the electromagnetic shielding effect of Example 1 is better than that of Examples 2 and 3. The reason is that in Examples 2 and 3, as the amount of HAC and sodium tetraborate increases, the weight ratio of MXene in the whole system decreases and the overall density increases, thus affecting its electromagnetic shielding effect.

[0043] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any transformations or substitutions that can be understood by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of the present invention.

Claims

1. A method for preparing MXene / modified polymer aerogel, characterized in that, include: First, take 3 ml of 10 mg / ml MXene dispersion, then add 15-60 mg of dopamine-grafted sodium hyaluronate. After it is completely dissolved, add 12-48 mg of sodium tetraborate and continue stirring for 30 min. Then, put it into a container filled with liquid nitrogen, so that the metal base of the mold is in contact with the liquid nitrogen for directional freezing, and freeze it at -10℃ for 2 h. Then, place it in a freeze dryer for freeze drying to obtain MXene / modified polymer aerogel. The preparation steps of the dopamine-grafted sodium hyaluronate include: Step 1: Prepare a 0.01 mol / L PBS buffer solution: Weigh 7.9g sodium chloride, 0.2g potassium chloride, 0.24g potassium dihydrogen phosphate and 1.8g dipotassium hydrogen phosphate and add them to a 500ml beaker containing 300mL deionized water. Dissolve the solution by magnetic stirring at room temperature, then transfer it to a 1L volumetric flask and add deionized water to make up to the final volume to obtain a 0.01mol / L PBS buffer solution. Store the solution at 4℃ after preparation. Step 2: Preparation of dopamine-grafted sodium hyaluronate: 1) At room temperature, weigh 1g of sodium hyaluronate and place it in a three-necked flask. Add 100mL of 0.01mol / L PBS buffer solution and stir until the sodium hyaluronate is completely dissolved. Then adjust the pH of the solution to 5. Add 0.286g of N-hydroxysuccinimide and 0.476g of 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide catalyst in sequence. After they are fully dissolved by stirring, purge with nitrogen for 30min. Add 0.566g of dopamine and react in an ice bath for 12h. 2) The crude product after the reaction was placed in a dialysis bag with a molecular weight cutoff of 14 kDa and dialyzed with deionized water for 2 days, changing the deionized water every 12 hours to remove the residual catalyst and unreacted monomers in the solution to obtain the grafted product. The dialyzed solution was freeze-dried to obtain dopamine-grafted sodium hyaluronate.

2. An MXene / modified polymer aerogel prepared by the preparation method as described in claim 1.

3. An application of the MXene / modified polymer aerogel as described in claim 2 in electromagnetic interference shielding.

Citation Information

Patent Citations

  • Method for improving adhesion property of polyacrylamide hydrogel, and resulting polyacrylamide hydrogel

    CN109651623A

  • ANFs / MXene composite electromagnetic shielding aerogel and preparation method thereof

    CN114516973A